PENGARUH HARGA KARET TERHADAP PRODUKSI PERKEBUNAN KARET DI PROVINSI JAMBI - Fransfali Haloho, Alfredo; Mara, Armen; Damayanti, Yusma (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2019)
This research was conducted to determine the development of rubber production and rubber prices in Jambi Province and to determine the effect of bokar prices, Sir 20 and world prices on rubber production in Jambi Province. The data used is time series from 1990 - 2016. The analytical method used is multiple linear regression. The results showed that the production and price of farmers at farm level, the price of sir 20 and world prices in Jambi Province in the period 1990 - 2016 fluctuated with the average growth rate of each of which was 96% of production, the price of farmers at 543%, sir 20 prices are 52.4% and world prices are 44%.The Cobb Douglas production function is used to determine the effect of farmer-level bokar prices, sir 20 prices and world rubber prices as independent variables. The results of the analysis show that only the farmer-level bokar price has a significance level below 0.05, that is 0.0013, this farmer-level bokar price is one that has a significant effect on rubber production because the farmer-level bokar prices are quickly known by farmers, while the price of sir 20 and world prices are generally only industries that know about it, so farmers only follow the benchmark of the farmer-level bokar price. These rubber plants are generally plants that are ready to produce at any time unlike oil palm and food crops, oil palm takes 14 days to be harvested and food crops can be harvested for only once every four months. Therefore, when the price of bokar rises, farmers will tap their rubber trees more often because they can immediately feel the results of their work.